Pengembangan Media Interaktif Berbasis Artificial Intelegence (AI) untuk Mempermudah Pembelajaran Bahasa Arab: Pengembangan Media Interaktif Berbasis Artificial Intelegence (AI) untuk Mempermudah Pembelajaran Bahasa Arab - Wulandari Samsudin, Nur Fajri; Bt. H. Bahri, Ratni; Amrullah, M. Kholis (ELOQUENCE : Journal of Foreign Language, 2024)
Background: Educational technology plays a significant role in the teaching and learning process, particularly in addressing various challenges educators and students face. In this digital era, innovative learning technologies, such as artificial intelligence (AI), were increasingly applied, especially in school Arabic language instruction. Purpose: This study aimed to develop AI-based interactive media to facilitate Arabic language learning at Madrasah Tsanawiyah Al-Muhajirin Parungi. Methods: This research utilized the Research and Development (R&D) process. Results and Discussion: The findings indicated that teachers and students required practical learning media for Arabic language acquisition. Following the analysis, interactive press was developed, featuring engaging designs, audio-visual integration, and leveraging AI-based applications such as text-to-speech (TTS) and background image erasers. This media product was validated by experts, achieving a score of 90%, which indicated high feasibility. The media was then implemented with students and teachers, receiving positive feedback, with 88% of teachers and 86% of students affirming that the media was highly suitable for use. Conclusion and Implication: This study successfully developed AI-based interactive media that proved to be highly effective, showing significant improvements in students’ Arabic language learning outcomes. Statistical tests revealed a p-value smaller than 0.05 and an N Gain Score of 67.92%, indicating the effectiveness of the media in enhancing students’ Arabic language skills. This innovation was expected to positively impact learning at Madrasah Tsanawiyah Al-Muhajirin Parungi.